FACTORS INFLUENCING INTEGRATED MANAGEMENT OF NEWBORN CHILDHOOD ILLNESSES (IMNCI) UPTAKE AMONG CHILDREN IN CMH GILGIT, PAKISTAN - BURIRO, NA; FATIMA, A; KHAN, SA; ZEHRA, SE; KUMAR, V; JOKHIO, F; KHOSO, MH (Biological and Clinical Sciences Research Journal, 2024)
In developing countries, about 9 million children die before reaching the age of 5 every year, with 70% of these deaths attributable to five central diseases (measles, diarrhea, pneumonia, malaria, and malnutrition). The World Health Organization (WHO) and the United Nations Children’s Fund (UNICEF) have recognized the importance of early care-seeking and have developed the "integrated management of childhood illness" to promote proper healthcare practices within families and communities and decrease the mortality rate of children under five in developing countries. This study aimed to improve the health-seeking behaviour of mothers and reduce the burden of disease in children under five, with specific objectives to assess the factors affecting the uptake of integrated management of childhood illness (IMNCI) and the health-seeking behaviour of mothers. Using a structured questionnaire, a hospital-based cross-sectional study was conducted on 156 randomly selected parents of patients at CMH, Gilgit, from August to December 2016. The chi-square test determined associations between different factors and mothers’ health-seeking behaviour. The results showed strong associations at p=0.05 and a 95% confidence interval with n=156. Strong associations were found between the first care given and the head of the family (p=0.02) and between health problems and the head of the family (p=0.01). The findings also indicated a strong relationship between the head of the family and restrictions when seeking care for a sick child (p=0.00). Maternal education positively impacts health outcomes, leading to fewer family restrictions, early identification of problems, and improved decision-making when seeking healthcare.